Efeitos do resveratrol, do suco de uva e do vinho tinto nos biomarcadores de estresse oxidativo e na atividade de ectoenzimas em ratos diabéticos - Schmatz, Roberta (2012)
Diabetes mellitus is a major public health problem throughout the world. The chronic hyperglycemia present in the diabetic state is associated with increase of oxidative stress, which has been appointed to play a central role in the development and progression of diabetic complications. Changes in the platelet morphology and function observed in diabetes have been considered as important aggravating to the pathogenesis of vascular complications in this endocrinopathia. The extracellular nucleotides ATP, ADP and nucleoside adenosine are known to regulate various physiological processes in the vascular system, including platelet aggregation, vascular tone and cardiac functions. The control of extracellular levels of these molecules and consequent purinergic signaling induced by them is controlled by a variety of enzymes such as NTPDases (Nucleotide Triphosphates Diphosphohydrolase), E-NPPs (Ecto-Nucleotide Pyrophosphatase Phosphodiesterases), 5'-nucleotidase and adenosine deaminase (ADA). On the other hand, studies have revealed a number of beneficial actions of red wine and grape juice, which can be attributed to high concentrations of polyphenols presents in these beverages, mainly of resveratrol, which presented antioxidant and antiplatelet properties. In this context, the objective of this study was to investigate the effect of resveratrol, of red wine and of grape juice in the biomarkers of oxidative stress in liver and kidney, in the ectoenzimas activities in platelets and platelet aggregation of streptozotocin-induced diabetic rats. In addition, tests were performed in vitro with the polyphenols resveratrol, quercetin, rutin, caffeic acid and gallic acid on the activity of ectonucleotidases, ADA and platelet aggregation in diabetic and control rats. The results showed an increase in the levels of lipid peroxidation in liver and kidney of diabetic rats and treatment with resveratrol (10 and 20 mg/kg) prevented this increase. The activities of catalase (CAT), superoxide dismutase (SOD) and aminolevulinic acid dehydratase (-ALA-D) and the levels of non protein thiols (NPSH) and vitamin C presented a significant decrease in diabetic rats. However, the treatment with resveratrol (10 and 20 mg/kg) was able to prevent the decrease in the antioxidant defenses in diabetic rats. In relation to NTPDase, E-NPP, 5'-nucleotidase and ADA, there was an increase in activity of these ectoenzimas in platelets of diabetic rats accompanied by an increase in platelet aggregation in these animals. Treatment with resveratrol (10 and 20 mg/kg), grape juice and red wine increased the activity of NTPDase, E-NPP and 5'-nucleotidase and prevented the increase in ADA activity in diabetic rats. Platelet aggregation significantly decreased in diabetic rats treated with grape juice and red wine. In the in vitro tests, resveratrol, caffeic acid, and gallic acid increased ATP, ADP and AMP hydrolysis, while quercetin and rutin decreased the hydrolysis of these nucleotides in platelets of diabetic rats. The ADA activity and platelet aggregation were reduced in platelets of diabetic rats in the presence of all polyphenols tested in vitro. The results described here suggest that resveratrol could have a protector effect against hepatic and renal damage induced by oxidative stress in the diabetic state, which was evidenced by the capacity of this polyphenol to modulate the antioxidant defense and to decrease the lipid peroxidation in these tissues. In addition, resveratrol, red wine and grape juice as well as caffeic acid, gallic acid, quercetin and rutin were able to modulate the ectoenzimas activities and decrease platelet aggregation could contribute to the prevention and reduction of platelet abnormality and consequently vascular complications in diabetic state.